Endoscopic Management of Upper and Lower Ureteric Stones Using Pneumatic Lithotripter: A Retrospective Medical Records Review - Mustafa M; Al Zabadi H; Mansour S; Nabulsi A (Research and Reports in Urology, 2023)
Mahmoud Mustafa,1,2 Hamzeh Al Zabadi,3 Shaden Mansour,1 Aya Nabulsi1 1Department of Urology, An-Najah National University Hospital, An-Najah National University, Nablus, Palestine; 2Medicine Department, Faculty of Medicine and Health Sciences, An-Najah National University, Nablus, Palestine; 3Public Health Department, Faculty of Medicine and Health Sciences, An-Najah National University, Nablus, PalestineCorrespondence: Mahmoud Mustafa, Department of Urology, An-Najah National University Hospital, An-Najah National University, Nablus, Palestine, Email dr_mahmoud681@yahoo.com Hamzeh Al Zabadi, Public Health Department, Faculty of Medicine and Health Sciences, An-Najah National University, Nablus, Palestine, Email halzabadi@gmail.comBackground: In this study we aimed to assess and compare the rate of sem-irigid ureterorenoscope in the treatment of upper and lower ureter stones through pneumatic lithotripsy (PL).Materials and Methods: Ninety-two patients with a mean age±SD of 45± 15years who had had a surgical procedure performed by the same experienced surgeon between January 2013 and July 2015 were included in the study. The mean±SD stone size was 8.8± 2.6 mm. Forty-two of the patients (45.7%) had upper ureter stones and 50 (54.3%) had lower ureter stones in order to increase the success rate and avoid stone migration. The medical files of the patients were reviewed regarding age, sex, stone size, stone location, success rate, complications, and presence of hydronephrosis. Success was operationally defined as the complete fragmentation of stone to very small parts that could pass or complete extraction of the stone.Results: Eighty-four of the patients were stone free (91%). The success rates for patients with upper or lower ureteric stones were 93% and 90%, respectively (P=0.63). There were no complications during the operation. However, 4 patients (4.4%) had postoperative complications in terms of urinary tract infection or urosepsis. Those were accurately managed by the suitable medical treatment.Conclusion: Semi-rigid ureterorenoscopy by using PL was a safe and practical treatment option for managing the upper and lower ureter stones. Performing the tips and tricks of ureterorenoscopy by an experienced surgeon seems to enhance the success rate, especially in upper ureter stones.Keywords: pneumatic lithotripsy, Palestine, ureterorenoscopy, ureter stone, ureter